Empowering farmers through practice of supportive agro communities - Ismail, Ismi Arif; Mohamed Haris, Nur Bahiah; Krauss, Steven Eric; Hamzah, Azimi (IDOSI Publications, 2014)
The role of extension agents in facilitating and inspiring farmers of the future is undeniably important in sustaining the agriculture sector globally for years to come. They are the agents that sustain the synergistic working relationship among farmers, government, private organizations, NGOs and the community at large. However, studies on how extension supports farmers are highly needed to develop supportive agro communities of practice. This paper discusses how research and extension collaboration empower farmers to engage themselves in continuing professional development activities and to strategize towards excellence. It explores the career experiences of novice and experienced farmers juggling their various tasks in agricultural work practice. Seven farmers participated in this qualitative study. Analysis of farmers’ career experiences was carried out through a series of interviews, document analysis and a literature review on a situated lifelong learning process undertaken within agriculture. How communities of practice in agriculture provide an educational process for farmers is also discussed. Their stories are valuable in revealing the learning experiences of farmers surviving the challenges in the agricultural world. Farmers, policy makers, researchers, academics and people working in agriculture can learn a great deal about what individuals and institutions need to do to develop farmers, personally and professionally. This paper also discusses strategies towards developing supportive agro communities of practice. The findings of this study aim to contribute to better agricultural work practice through a dynamic and systematic research and extensive collaboration, globally and locally.